The influence of diet, gamma-linoleic acid (GLA) and eicosapentaenoic acid (EPA) on low density lipoprotein metabolism in African vervet monkeys - Tromp, Erna (Stellenbosch : Stellenbosch University, 2012)
One copy microfiche.